Sustained relief of ongoing experimental neuropathic pain by a CRMP2 peptide aptamer with low abuse potential. Issue 9 (September 2016) - Xie, Jennifer Y.; Chew, Lindsey A.; Yang, Xiaofang; Wang, Yuying; Qu, Chaoling; Wang, Yue; Federici, Lauren M.; Fitz, Stephanie D.; Ripsch, Matthew S.; Due, Michael R.; Moutal, Aubin; Khanna, May; et al.
Abstract : Abstract: Uncoupling the protein–protein interaction between collapsin response mediator protein 2 (CRMP2) and N-type voltage-gated calcium channel (CaV2.2) with an allosteric CRMP2-derived peptide (CBD3) is antinociceptive in rodent models of inflammatory and neuropathic pain. We investigated the efficacy, duration of action, abuse potential, and neurobehavioral toxicity of an improved mutant CRMP2 peptide. A homopolyarginine (R9)-conjugated CBD3-A6K (R9-CBD3-A6K) peptide inhibited the CaV2.2–CRMP2 interaction in a concentration-dependent fashion and diminished surface expression of CaV2.2 and depolarization-evoked Ca 2+ influx in rat dorsal root ganglia neurons. In vitro studies demonstrated suppression of excitability of small-to-medium diameter dorsal root ganglion and inhibition of subtypes of voltage-gated Ca 2+ channels. Sprague-Dawley rats with tibial nerve injury had profound and long-lasting tactile allodynia and ongoing pain. Immediate administration of R9-CBD3-A6K produced enhanced dopamine release from the nucleus accumbens shell selectively in injured animals, consistent with relief of ongoing pain. R9-CBD3-A6K, when administered repeatedly into the central nervous system ventricles of naive rats, did not result in a positive conditioned place preference demonstrating a lack of abusive liability. Continuous subcutaneous infusion of R9-CBD3-A6K over a 24- to 72-hour period reversed tactile allodynia and ongoing pain, demonstrating a lack of tolerance over this time course. Importantly, continuous infusion of R9-CBD3-A6K did not affect motor activity, anxiety, depression, or memory and learning. Collectively, these results validate the potential therapeutic significance of targeting the CaV-CRMP2 axis for treatment of neuropathic pain. Abstract : Supplemental Digital Content is Available in the Text.R9-CBD3-A6K, a calcium-channel allosteric inhibitory peptide, reversed tactile hypersensitivity and relieved ongoing neuropathic pain after immediate or sustained subcutaneous administration in rats.